Eradicating extreme poverty in Bangladesh: national strategies and activities - Qayum, Nayma; Samadder, Mrinmoy (Brac University, 2019)
Although Bangladesh has achieved fairly steady economic growth, as of 2011, almost half of its population still lived in extreme poverty. As a result, the Government of Bangladesh and its development partners have recently started to target the extreme poor in many development policies and programmes. As part of a BRAC Advocacy Unit project titled National Policy Advocacy for CFPR-TUP, this study maps the current status of national-level policies and programmes that address extreme poverty in Bangladesh. Research methods include analysis of national strategies, project evaluations, academic literature, print media, and interviews with national stakeholders - academics, policymakers, development practitioners, and journalists. The study found existing poverty classifications as dated, and overlapping. Mostly linear in nature, these classifications did not represent categorical sub-groups of the poor. Development actors implemented multiple, overlapping programmes which often failed to distinguish between short-term social protection, and longer-term poverty alleviation. Increased dialogue between stakeholders, sharing organizational experiences, and collaboration on a national strategy can improve the quality of extreme poverty initiatives in Bangladesh.